Kebijakan Hukum Pidana Terhadap Kejahatan Penguntitan Berbasis Elektronik untuk Tujuan Seksual - Agung Liawi, Aldias; Muhammad Sofyan, Andi; Adhyanti Mirzana, Hijrah (Universitas Islam Negeri Alauddin Makassar, 2023)
Problems regarding the regulation of electronic-based sexual violence crimes are unclear and require more detailed elaboration, especially in the case of stalking crimes. The research method is normative legal research and applies two approaches, namely, the Comparative and Conceptual approaches. The results showed that understanding the law itself, especially comparisons that aim to assume equality (there are similarities in various legal systems), has a definite goal that is of course related to the formal way of building the system (reviewing); moreover, it aims to unite one law because it is related to cyberstalking; it is universal and can be reached from various regions, not only in Indonesia. Law enforcement for cyberstalking cases in Indonesia can be linked to provisions in the Criminal Code, the ITE Law, and the Pornography Law. So that the provisions in the TPKS Law that regulate electronic-based stalking for sexual purposes have not yet been implemented.